An exploratory study of factors motivating Mexican women to undertake and continue with nutritional programs. Issue 3 (2nd July 2020) - Rodriguez, Rachel; Quintanilla, Claudia
Abstract: The purpose of this paper is to study and provide a framework for the motivations of women to engage in and maintain a nutritional program in Mexico. Focusing on a physician–dietician counseling program, 10 in-depth interviews were conducted with women age 30–60 engaged in the program. Two different sets of motivations for women were found, intrinsic and extrinsic, consistent with the self-determination theory. A model presents each set of motivations including subsets that explain specifically what makes women want to continue a nutrition program. Also, marketing implications from these motivations are discussed.